The Role of the Prosecutor's Office in Eradicating Criminal Acts of Corruption in Aceh Tamiang Regency - Razi, Fakhrur; Zarzani, T. Riza (PT. Multidisciplinary Press Indonesia, 2024)
This study examines the role of the Attorney General's Office in combating corruption in Aceh Tamiang, Indonesia. Corruption poses a significant threat to societal welfare, undermining economic stability and eroding public trust in government institutions. The research emphasizes the critical functions of the Attorney General’s Office, particularly in their capacity as both prosecutors and investigators in corruption cases. It highlights the legal framework governing their authority and outlines specific initiatives aimed at preventing and addressing corrupt practices. The study reveals that challenges persist, including the complexity of cases, lack of cooperation from witnesses, and the influence of powerful actors shielding corrupt individuals. Furthermore, the findings indicate that successful corruption eradication requires collaborative efforts among law enforcement agencies, increased public awareness, and robust legal instruments. This paper contributes to the understanding of legal mechanisms in anti-corruption efforts and suggests actionable recommendations to enhance the effectiveness of the Attorney General's Office in Aceh Tamiang. Ultimately, it underscores the necessity of a comprehensive approach involving multiple stakeholders to restore integrity and transparency within public administration.